Pengembangan Sistem Informasi Manajemen Pelaporan Sarana dan Prasarana Studi pada Fakultas Ilmu Komputer Universitas Brawijaya - Danniar Reza Firdausy; Satrio Agung Wicaksono; Fajar Pradana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Faculty of Computer Science (FILKOM) Brawijaya University is a faculty under Brawijaya University, which can not be separated from the use of infrastructure facilities in organizing lecturing activities. As those activities goes by, those infrastructure facilities will be damaged which current solution is by the academic community FILKOM report to the worker Direct equipment orally or through the E-Complaint website of Universitas Brawijaya. The problem that arises from the process of reporting the complaint is the difficulty in identifying the infrastructure being reported so that it takes a long identification time of between 4 to 6 minutes. Based on these problems, Reporting and Maintenance Assets Management Information System that can be used by academic community to report complaints of infrastructure facilities in region of FILKOM UB are developed. This information system can also be used to track the status of reported complaints, either by the reporting party itself or by other academic community. The development of this information system is divided into 2 types, which are android applications for reporters and operators website for Equipment staff. Software development method used to develop this information system is using waterfall model. Then to test the implementation result of the reporting and status tracking function, validation testing, usability testing and time comparison testing were performed. From the testing stage it was found that with the availability of camera features and QR code scan, this information system can speed up the reporting process and also can accelerate the tracking of reporting status.